Sitotoksisitas Ekstrak Aspergillus fumigatus dari Daun Mekai (Albertisia papuana Becc.) terhadap Sel Kanker Payudara T47D dan MCF-7 - Hasnaul Maritsa; Soekarti Moeljopawiro; Rina Sri Kasiamdari (Biology Department, Faculty of Science and Technology, Univeristas Jambi, Indonesia, 2015)
The previous studies showed that the Albertisia papuana Becc. root have cytotoxicity on breast cancer. The A. papuana root toxicity on breast cancer could not only by plant secondary metabolism, but may be also by secondary metabolism of endophytes. Aspergillus fumigatus is one of endophytes that have anticancer agent. Endophytes can be distributed dynamically in whole of plant organ, one of them are leaves. Therefore the objective of this studies were to know the presence of A. fumigatus in A. papuana leaves, and the cytotoxicity of their secondary metabolism on breast cancer cells. The sample of A. papuana were collected from Botanical Zoo of Bogor, while T47D and MCF-7 cell lines were obtained of Tropical Medicine’s Faculty, UGM. Isolation of endophytes was done by growing leaves extract on water agar 2 % medium. Secondary metabolism was extracted from fermented broth using in ethyl acetat and n-butanol. The cytotoxicity was perform by MTT (3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide) assay. The result showed that A. fumigatus assosiated with A. papuana leaves. Ethyl acetat extract from fermented A. fumigatus both on T47D and MCF-7 cell lines had lower (IC50. 50, 444 µg/ml and 59 µg/ml) than n-butanol (IC50. 103, 398 µg/ml and 127,188 µg/ml. It could be said that A. fumigatus from A. papuana leaves could induce cytotoxicity on T47D and MCF-7 breast cancer cells.